Reconnoitering the Status of Outdoor Education: A Case Study of Lodhrān-Bahawalpur, Pakistan - Ahmad, Asma; Murtaza, Khan Ghulam; Hasan, Murtaza (European Journal of Applied Sciences, 2023)
Outdoor education gives opportunities for students to improve the learning methodology, enhance interdisciplinary matters and boost up the relationship with people and the environment. This research study investigates the status of outdoor education, students' and teachers' perception and experience at the college level in the joint District of Lodhrān-Bahawalpur, Pakistan. The study was confined to 50 different public and private schools and colleges, interviewing 150 teachers and 300 students using the cluster random sampling method. The descriptive research methodology was used to compare the analysis of the collected data through SSPS software. The objective of the study was to examine the students and teachers' perceptions regarding outdoor education problems, to explore the major issues of outdoor training programs, to find out the main reasons and causes behind these problems, and to give the recommendation to overcome these problems and possible available solutions for the issues.